Advances in electronic materials for clean energy conversion and storage applications - Khan, Aftab Aslam Parwaz; Nazim, Mohammed; Asiri, Abdullah M. (Woodhead Publishing series in electronic and optical materials, 2023)
Advances in Electronic Materials for Clean Energy Conversion and Storage Applications reviews green synthesis and fabrication techniques of various electronic materials and their derivatives for applications in photovoltaics. The book investigates recent advances, progress and issues of photovoltaic-based research, including organic, hybrid, dye-sensitized, polymer, and quantum dot-based solar cells. There is a focus on applications for clean energy and storage in the book. Clean energy is defined as energy derived from renewable resources or zero-emission sources and natural processes that are regenerative and sustainable resources such as biomass, geothermal energy, hydropower, solar and wind energy. Materials discussed include nanomaterials, nanocomposites, polymers, and polymer-composites. Advances in clean energy conversion and energy storage devices are also reviewed thoroughly based on recent research and developments such as supercapacitors, batteries etc. Reliable methods to characterize and analyze these materials systems and devices are emphasized throughout the book. Important information on synthesis and analytical chemistry of these important systems are reviewed, but also material science methods to investigate optical properties of carbon-nanomaterials, metal oxide nanomaterials and their nanocomposites. Reviews the latest advances in electronic materials synthesis, fabrication and application in energy Discusses green, cost-effective, simple and large-scale production of electronic materials Includes critical materials and device characterization techniques that enhance our understanding of materials' properties and measure device performance.